Can AI Bridge the Productivity Gap of an Aging Workforce? - Bizjak Ferjan, Maruša; Debelak, Katja (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The aging global workforce poses significant challenges for organizations striving to sustain productivity amidst the physical and cognitive decline associated with aging. Artificial intelligence (AI) emerges as a transformative tool, offering solutions to enhance the capabilities of older employees, automate routine tasks, and support informed decision-making. This paper explores the potential of AI to counteract productivity losses linked to workforce aging through a comprehensive review of existing research. It synthesizes insights on the effects of aging on employee productivity, examines how AI can complement and augment the contributions of older employees, and evaluates the broader implications of AI integration on organizational efficiency. By exploring exploring the interplay between AI’s potential and workforce aging and providing recommendations for inclusive AI implementation, the paper aims to contribute to the ongoing discourse on how AI can foster a sustainable, productive, and inclusive work environment in the face of demographic changes.